Estetika Bunyi Repetisi dalam Kumpulan Puisi Jauh itu Dekat Karya Tri Mulyono dan Implikasinya terhadap Pembelajaran Bahasa Indonesia di SMA - Umairoh, Umi; Mulyono, Tri; Anwar, Syamsul (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The purpose of this research was to describe the repetition in the collection of the poetry Jauh itu Dekat by Tri Mulyono and and describe its implications for learning Indonesian in high school. The research method used qualitative descriptive. This study used an objective approach. The data source in the study was 19 poems the collection of the poetry Jauh itu Dekat karya Tri Mulyono, published in 2020 by Satria Publisher. The research instrument is the researcher. The collection technique uses reading techniques and note taking techniques. Data analysis technique used analysis descriptive by means of reduction, categorization, and conclusions. Test the validity of the data using the validity of advisors who are expert advisors in the field and discussions with colleagues. The results showed that the eight repetition in the collection of the poetry Jauh itu Dekat by Tri Mulyono. The eight repetitions are epizeuxis, tautotes, anaphora, epistrophe, simploke, mesodiplosis, epanalepsis, and anadiplosis. The used of repetition is specially designed by the writer collection of the poetry Jauh itu Dekat by Tri Mulyono  to give a rhythm that adds to the aesthetic value of the poem.